INTERPRETACIÓN HERMENÉUTICA CRÍTICA DE UN CASO DE NORMATIVIDAD EDUCATIVA: La constitución española de 1978 y la ruptura del “pacto constitucional educativo” - Camacho, Guillermo Miranda (Universidad de Costa Rica, 2022)
This article is inserted within the framework of the critical theory of educationalnormative. It follows the methodology of a case study, adopting Jürgen habermas’smodel of repression of generalizable interests as a critical hermeneuticalinterpretation frame. The object of interpretation is the breakup of the constitutionaleducation pact, stipulated in Article 27 of the Spanish Constitution of 1978, with theapproval of the Law of the Statute of Educational Institutions (LOECE in Spanish).